Determinants and impact of diagnostic interval in bone sarcomas: A retrospective cohort study. Issue 3 (16th December 2022) - Sasi, Archana; Ganguly, Shuvadeep; Biswas, Bivas; Pushpam, Deepam; Kumar, Akash; Agarwala, Sandeep; Khan, Shah Alam; Kumar, Venkatesan Sampath; Deo, Suryanarayana; Sharma, Daya Nand; Bakhshi, Sameer
Abstract: Background: Diagnostic delays in cancers are frequent in developing countries due to poor health infrastructure. Existing literature from developed countries suggests that diagnostic interval in bone sarcomas is primarily dictated by tumour biology with no impact on survival. This study evaluates the social and biological determinants of the diagnostic interval in bone sarcomas in a resource‐challenged setting and assesses its impact on treatment outcomes. Methods: A retrospective single‐institutional study was conducted on patients with high‐grade bone sarcomas recorded in the sarcoma clinic database between 2003 and 2018. Baseline clinical characteristics and treatment outcomes were recorded. Logistic regression was performed to assess the impact of baseline clinical and social characteristics (distance from treating centre and rural vs. urban residence) on the diagnostic interval. Further, the impact of diagnostic interval on histologic response to neoadjuvant chemotherapy, amputation requirement in extremity sarcomas and survival was evaluated. Results: A total of 1227 patients were included for analysis. The median diagnostic interval was 4 months (3–7 months). Age above 18 years, Ewing sarcoma (ES) diagnosis, absence of fever at presentation and tumour size above 7.5 cm were predictors of a longer diagnostic interval (>4 months). The length of the diagnostic interval did not impact amputation requirement or survival outcomes. However, the proportion of patients with good necrosis post‐neoadjuvant chemotherapy was lower among patients with longer diagnostic intervals (25% vs. 34·16%; p ‐value = .04). Conclusion: Tumour characteristics rather than social factors determined the diagnostic interval. Diagnostic interval did not impact survival outcomes even in a resource‐constrained setting.